Decision Support System Honorary Employee Performance Appraisal with TOPSIS method the Public Works Department and Spatial Deli Serdang - Tasman, Abel; Simanjorang, R. Mahdalena (Information Technology and Science (ITScience), 2020)
Honorary employee performance appraisal on the Department of Public Works and Spatial Deli Serdang conducted on 10 honorary staff as samples of employee performance appraisal of data as material for consideration of the continuation of the cooperative relationship for the future budget. Components of employee performance appraisal onconducted on 10 honorary staff as samples of employee performance appraisal of data as material for consideration of the continuation of the cooperative relationship for the future budget. Components of employee performance appraisal on the Department of Public Works and Spatial Deli Serdang namely work performance, performance quantity, performance discipline, cooperation, and commitment. Problems with the employee performance appraisal process that occur due to unclear criteria and weight of the appraisal. A method in the decision support system can help the optimal decision making process that is TOPSIS method in Determining the performance appraisal of honorary employees. There are three employee performance weights, the which are very good, good, and quite good, from 10 employees Categorized by performance appraisal, after being applied with the TOPSIS method, Joko Suprapto Obtained value = 0.8394 and Suhendra value = 0.7862 both honorary employees are Categorized by assessment very good performance.